Genotype x environment interaction through AMMI analysis in sesame genotypes: Genotype x environment interaction through AMMI analysis in sesame genotypes - BHAGWAT SINGH; RAJANI BISEN (Journal of Oilseeds Research, 2020)
The present study investigates the magnitude of GxE interaction and stability of sesame genotypes over the environments. The results indicated that for seed yield/plant, the ASV values ranged from 0.186 to 2.363. Accordingly, genotypes SAVITRI, TMV-4, SSD-5, DSS-9 and RAJESHWARI were considered to be most stable, while YLM-17, CHANDANA, NIRMALA, USHA and PT-1 were less stable genotypes.